Exploring the students' perceptions of the usefulness of CLIL Modules and ICT integrated learning in English classroom - Kamsilawati Kamlun; Chang, Siew Lee; Suhaida Omar (PalArch Foundation, 2020)
This study outlines students‟ perceptions of the usefulness of the Content and Language Integrated Learning (CLIL) modules and ICT integrated learning in English lessons at a local public university. CLIL offers the ability to illustrate to students that both the material and language in CLIL lessons are given equal consideration. As it can be part of other subjects such as history, geography, arts and science, English is not a secluded, individual subject, so students should not be limited to only memorising grammar rules and performing grammar exercises in their workbook. The key purpose of this analysis is to explore first-year undergraduates' perceptions of the usefulness of the CLIL modules. Using reflective journal writing, this study used qualitative methods to gather students' views on how CLIL modules can boost English learning among undergraduates and to use ICT in CLIL lessons. There were 22 participants who were marked by the Malaysian University English Test (MUET) Bands 1 and 2 as low-intermediate English learners. The results showed positive feedback that the CLIL module is useful in their English lessons through the responses of the students. Most of the students said the lessons help to improve their understanding of English grammar as well as their communication abilities in English. This showed that in encouraging students to learn English with ICT in a modern way, CLIL plays a part.